Aflatoxin B1 degradation by culture and lysate of a Pontibacter specie. (October 2017) - Adebo, Oluwafemi Ayodeji; Njobeh, Patrick Berka; Sidu, Sibusiso; Adebiyi, Janet Adeyinka; Mavumengwana, Vuyo
Abstract: The presence of aflatoxin B1 (AFB1 ) along the food chain poses a significant threat, thus propelling the need for an effective approach to control it. This study was therefore, aimed at investigating AFB1 degradation of liquid cultures and lysates of an isolated Pontibacter sp. (VGF1). Liquid cultures, lysed bacterial cells in the absence (uninhibited lysates) and presence of protease inhibitors (protease inhibited lysates) were respectively incubated with AFB1 for 3, 6, 12, 24 and 48 h. AFB1 degradation was monitored during this period on high performance liquid chromatography (HPLC) and results obtained revealed that after 6 h of incubation, the protease inhibited (PI) lysates yielded a 65% AFB1 degradation, whereas after 12 h, no residual AFB1 was detected. Conversely, after 48 h of incubation, a significantly (p≤0.05) lower AFB1 degradation of 50 and 36% by the liquid culture and uninhibited lysate, respectively, were noted. It was further confirmed that the degradation mechanism was enzymatic. Data from cytotoxicity studies against human lymphocytes further demonstrated that extracts of biotransformed AFB1 were less toxic when compared to that of AFB1 . Findings from this study have demonstrated an alternative approach for the decontamination and biocontrol of AFB1 in various agricultural commodities. Highlights: Protease inhibition of lysates before cell lysis increased AFB1 degradation. In 12 hrs of incubation, no residual AFB1 degradation was detected. Bio-transformed extracts had reduced cytotoxicity on human lymphocytes.